The Effect Of Exercises Using External Distractions On the Accuracy of (10m) Penalty Shot For Futsal Players - Lazim, Asaad; Qassim, Ismael (Journal of Physical Education, 2017)
The training of players in conditions similar to the conditions of the games withexternal influences and stimuli help the players overcome many difficulties especially infutsal because it is a game of changing circumstances with multiple stimuli .The importanceof research lies in using game – like conditions by exposing the player to various stimuliwhich helps him in the future to develop concentration, that isolates unwanted stimuli andfocus on the accuracy of scoring during the penalty shot .The problem of research is the lackof attention to external distraction factors in any training module, especially in the penaltyshot .The aims of the research was preparing exercises that develop the accuracy of theplayers 'correction during penalty shots with external stimuli and distractions as well as torecognizing the effect of these exercises. The researcher used the experimental method. Thesubjects were (20) players from the college of languages. They were randomly divided intotwo equal experimental and controlling .The exercise were applied to the experimental groupfor eight weeks, three units per week as well as the same repetitions of the controlling groupwithout exposing them to any external effect. The results were presented through pre andposttests of the two groups. The researchers concluded were reached and concluded that theexercise of the effects of similar conditions of play has a positive effect on the developmentof the scoring performance and the accuracy penalty.